Cores and peripheries in a northern periphery: a case study in Finland - Pekka Kauppila (Fennia: International Journal of Geography, 2011)
During the last decades, peripheral rural areas have been faced with social and economic challenges, such as economic restructuring, unemployment, out-migration and ageing population. Due to declining traditional industries, tourism has often been highlighted as a vehicle to revitalize the economy in rural areas. The aim of the review is to conceptualize the regional development process of resorts in relation to their location municipalities at the local level in Finland. GIS (Geographical Information Systems) technology and georeferenced data, so called grid data, are utilized in the statistical socio-economic analysis of the four largest resorts – Levi, Ruka, Saariselkä and Ylläs – in the Finnish periphery. The study results show that the development process of the resorts has been very positive in terms of the indicators of regional development. Along with the absolute progressing, the relative importance of the resorts within their location municipalities has strengthened. The outcome of the study is presented in the classic core–periphery framework: the resorts are considered as cores and the surrounding area of those cores as a periphery. In consequence, there emerges a polarization process within the municipalities under study because of tourism development. It is obvious that the role of the resorts within the location municipalities in regional development will strengthen in the future. Generally speaking, from the viewpoint of the regional development of peripheral rural areas, the main challenge is to extend the positive socio-economic impacts of resorts, cores, to a wider geographical area, a periphery.